Child Marriage : A Critical Barrier to Girls’ Schooling and Gender Equality in Education - McCleary-Sills, Jennifer; Hanmer, Lucia; Parsons, Jennifer; Klugman, Jeni (Taylor and Francis, 2015)
Education is not only a human right, but also a powerful tool for women’s empowerment and a strategic development investment. There is a clear multiplier effect to educating girls; women who are educated are healthier, participate more in the formal labor market, earn more income, have fewer children, and provide better healthcare and education to their children compared to women with little or no education. The benefits of education thus transmit across generations as well as to communities at large. Where girls have greater educational and economic opportunities, they are more likely to pursue those opportunities than to have children in their teenage years. Yet a host of structural, social, and financial barriers prevent girls’ enrollment and completion of both primary and secondary school.